Analisis Interaksi Aliran Darah dan Pembuluh Serta Pengaruh Kebebasan Mesh Pada Simulasi Hemodinamik Berbasis Metode Elemen Hingga - Narendra Kurnia Putra; Bonfilio Nainggolan; Johanna Muliany; S Suprijanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Cardiovascular diseases are the worldâ€™s leading cause of death with significant death rates caused by abnormalities in vessels such as aneurysms and stenosis. These conditions can potentially cause blockage and thinning of vessels which may lead to heart attack, stroke, and bleedings. Recently, computational simulation methods are frequently used in blood flow analysis. These methods are frequently used in vascular fluid dynamics analysis which relate to the origin of a disease, efficacy prediction in installation of therapeutic instruments and complements the in vitro studies. This article presents an example of a simple vascular simulation to study the effect of blood flow with respect to vascular wall displacement. Furthermore, this research shows the importance of formal CFD pre-processing such as mesh independence testing which influences the simlation accuracy as well as vascular flow prediction and its effects on vascular wall displacement. In this research, it is concluded that the number of mesh elements affects the accuracy of vascular wall shear stress (WSS) calculations with average WSS difference of 0.8 Pa with no significant difference in wall displacement values. An average WSS of 1.95 Pa and a wall displacement of 5.7 Âµm are obtained from the blood flow simulation in this study.